Pseudo-Boolean Programming for Bivalent Optimization - Natesan, M. (My University, 1973)
This thesis introduces an effective computational algorithm making use of Boolean algebra for solving bivalent optimization problems with linear and nonlinear constraints. This method is a combination of the algorithm suggested by Hammer and the branch and bound method. The whole system of constraints is replaced by a single Boolean resolvent function and the solutions of this resolvent are found by branch and bound method which are found to be the feasible solutions of the system of constraints. Some practical applications are also discussed.
Title: Pseudo-Boolean Programming for Bivalent Optimization, Author: M. Natesan, Location: Thode